2012
DOI: 10.1007/s12094-012-0789-z
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microarray-based study of patients with lymph node-positive breast cancer shows tyrosine phosphorylation of signal transducer and activator of transcription 3 (tyrosine705-STAT3) is a marker of good prognosis

Abstract: These findings support the role of Phospho- STAT3 as an important independent prognostic marker in node-positive breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…High total STAT3 was significantly associated with improved outcome in three studies [16, 18, 19], and with poor outcome in one study [20]. Ph-STAT3 expression was not associated with breast cancer survival in two studies [13, 21], and was associated with improved survival in large cohort of patients [22], patients with lymph node positive tumours [23], and patients treated with adjuvant chemotherapy [24]. In contrast, ph-STAT3 was a significant predictor of worse survival in one study [17] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…High total STAT3 was significantly associated with improved outcome in three studies [16, 18, 19], and with poor outcome in one study [20]. Ph-STAT3 expression was not associated with breast cancer survival in two studies [13, 21], and was associated with improved survival in large cohort of patients [22], patients with lymph node positive tumours [23], and patients treated with adjuvant chemotherapy [24]. In contrast, ph-STAT3 was a significant predictor of worse survival in one study [17] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The study of phosphorylation in signal transduction events is especially important in pathways that are known to be dysregulated in disease states. Recent studies have defined a role for measuring the kinetics of phosphorylation events in not only the diagnosis/prognosis of diseases (Mackenzie et al, 2012; Sonnenblick et al, 2012; Woost et al, 2011), but also the efficacy of therapies, such as with the bcr/abl kinase inhibitor Imatinib, directed towards epigenetic alterations. (Druker et al, 2001; Hedley et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a number of well-performed studies have suggested that the activation of STAT3 might not be uniformly associated with increased malignancy, and that in some circumstances STAT3 might act as a functional tumor suppressor or its activation may be associated with an improved prognosis [7,8,9,10]. Thus, dissecting these dichotomous roles is an important question in cancer biology.…”
Section: Introductionmentioning
confidence: 99%